Application of δ18O, δ13CDIC, and major ions to evaluate micropollutant sources in the Bay of Vidy, Lake Geneva†. Issue 1 (3rd March 2016) - Halder, Janine; Pralong, Charles; Bonvin, Florence; Lambiel, Frederic; Vennemann, Torsten W.
Abstract : Waters were sampled monthly from a profile at the wastewater outlet and a reference point in the Bay of Vidy (Lake Geneva) for a year. The samples were analyzed for 18 O/ 16 O of water, 13 C/ 12 C of dissolved inorganic carbon (DIC), major ions, and selected micropollutant concentrations. δ 18 O values, combined with the major ion concentrations, allowed discharged waste and storm-drainage water to be traced within the water column. On the basis of δ 18 O values, mole fractions of wastewater (up to 45 %), storm-drainage (up to 16 %), and interflowing Rhône River water (up to 34 %) could be determined. The results suggest that the stormwater fractions do not influence micropollutant concentrations in a measurable way. In contrast, the Rhône River interflow coincides with elevated concentrations of Rhône River-derived micropollutants in some profiles. δ 13 C values of DIC suggest that an increase in micropollutant concentrations at the sediment–water interface could be related to remineralization processes or resuspension.